Concentration-dependent effects of sodium cholate and deoxycholate bile salts on breast cancer cells proliferation and survival - Gándola, Yamila Belén (2020)
Bile acids (BAs) are bioactive molecules that have potential therapeutic interest and their derived salts are used in several pharmaceutical systems. BAs have been associated with tumorigenesis of several tissues including the mammary tissue. Therefore, it is crucial to characterize their effects on cancer cells. The objective of this work was to analyse the molecular and cellular effects of the bile salts sodium cholate and sodium deoxycholate on epithelial breast cancer cell lines. Bile salts (BSs) effects over breast cancer cells viability and proliferation were assessed by MTS and BrdU assays, respectively. Activation of cell signaling mediators was determined by immunobloting. Microscopy was used to analyze cell migration, and cellular and nuclear morphology. Interference of membrane fluidity was studied by generalized polarization and fluorescence anisotropy. BSs preparations were characterized by transmission electron microscopy and dynamic light scattering. Sodium cholate and sodium deoxycholate had dual effects on cell viability, increasing it at the lower concentrations assessed and decreasing it at the highest ones. The increase of cell viability was associated with the promotion of AKT phosphorylation and cyclin D1 expression. High concentrations of bile salts induced apoptosis as well as sustained activation of p38 and AKT. In addition, they affected cell membrane fluidity but not significant effects on cell migration were observed. In conclusion, bile salts have concentration-dependent effects on breast cancer cells, promoting cell proliferation at physiological levels and being cytotoxic at supraphysiological ones. Their effects were associated with the activation of kinases involved in cell signalling.